Mengevaluasi Pengungkapan ESG Perusahaan: Tingginya Potensi Greenwashing dalam Sustainability Report - Lingga Sekar Arum; Harry Z. Soeratin; Munasiron Miftah (Program Studi Magister Manajemen Universitas Advent Indonesia, 2024)
This study aims to evaluate the potential for greenwashing in companies' sustainability reports by investigating the internal factors that influence the level of ESG integration in their financial reporting. The research employs a qualitative approach using the literature review method to explore and synthesize findings from various relevant literature sources. The literature search strategy involves combining keywords such as